Amino Acid Salt Catalyzed Asymmetric Synthesis of 1,2-Diols with A Quaternary Carbon Center - Wu, Quanquan; Liu, Shulei; Wang, Fangyuan; Li, Qingqing; Cheng, Kangli; Li, Juan; Jiang, Jun (Synlett, 2015)
Enantioenriched 1,2-diols with a quaternary carbon center have great potential in the preparation of natural and biologically active compounds, but remain challenging synthetic targets which demand for both good diastereo- and enantioselectivity. As part of our continuous effort to explore the unique catalytic activities of amino acid salts in the asymmetric synthesis, herein, we wish to report an amino acid salt catalyzed direct aldol reaction between hydroxyacetone and α-keto esters, which afforded the 1,2-diols with a quaternary carbon center in high diastereo- and enantioselectivities.
Keywords: 1,2-diols; quaternary carbon center; amino acid salts; asymmetric catalysis